Penerapan AAUPPL oleh Administrasi (Suatu Upaya Menuju “Clean and Stable Government”) - Jazim Hamidi (Unisia, 2007)
Administrative judges can apply the AAPPL to examine validity of administrative decisions of state by means of connecting relevance substantive legal norms through deductive reasoning. There are two standards to qualify as to whether an administrative decision is in contradiction with the AAUPPL: written legal norms and unwritten legal norms in form of the AAUPPL. The AAUPPL is an effective means of control to examine administrative policies or decisions that are not touched upon by written laws, and, hence will reduce state policies and decisions that are legally immune. Keywords: administrative decisions, judges, control, validity.